2019
DOI: 10.5812/sdme.80871
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitating Factors of Communication in Iranian Educational Health Care Centers: A Systematic Review

Abstract: Context: Communication, as an essential human skill, is one of the most influential factors in the performance of healthcare workers. In fact, the establishment of effective communication with the recipients of healthcare services and patients can increase their satisfaction and quality of life. Due to the paucity of comprehensive research in this area, the present study aimed to investigate the barriers and facilitating factors concerning communication among healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…If there is not enough knowledge about these cases, communication will be impaired. Overall, the HCP should be in line with the clients culture (23). The results of Schinkel et al's research also showed that from the perspective of immigrant patients, it is very important to pay attention to cultural barriers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…If there is not enough knowledge about these cases, communication will be impaired. Overall, the HCP should be in line with the clients culture (23). The results of Schinkel et al's research also showed that from the perspective of immigrant patients, it is very important to pay attention to cultural barriers.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have pointed to the role of environmental factors as barriers to effective communication (23,24). One prevalent barrier to communication is environmental noise.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have pointed to the role of environmental factors as barriers to effective communication. 21 , 26 One prevalent barrier to communication is environmental noise. Environmental noise, further defined as equipment- and staff-related noise, usually refers to any extraneous sounds within the operational environment, such as conversation, tools, alarms, and ambient sounds from machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial abilities, known as life skills, refer to stabilizing an effective interpersonal relationship for assuming social responsibility, making decisions, and solving conflicts without resorting to actions harmful to the individual or others [ 1 ]. In health care field, medical students (MSs), tomorrow’s practitioners, are known to have daily direct/indirect interactions with colleagues, families, and health-care recipients [ 2 ]. Hence, MSs are required to get appropriate social skills [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific data proved that staff who are skilled in communication are faced with fewer problems, make fewer errors, spend fewer resources, and handle difficulties more efficiently [ 8 ]. In contrast, failure in communication has adverse effects, such as increased rate of misdiagnosis, increased medical errors, patient dissatisfaction, and noncompliance with health care [ 2 ]. Some studies have demonstrated that inadequate information sharing and communication errors due to professionals’ hesitancy to speak-up lead to adverse patient outcomes [ 9–11 ].…”
Section: Introductionmentioning
confidence: 99%